Midlife Career Change to Tenured/Tenure-Track and Non-Tenure-Line Faculty: Shared and Unique Challenges, Supports, and Strategies - Catherine A Cherrstrom (Adult Education Research Conference, 2018)
These studies investigated the career transition and strategies of women midlife career changers to tenured/tenure-track and non-tenure-line faculty. Major findings included a career transition process and related challenges, supports, and strategies and feature participant voices.
Keywords: career transition; career change; midlife; faculty; higher education